2017
DOI: 10.1111/asj.12916
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the quality and hygiene parameters of bulk Italian Mediterranean buffalo (Bubalus bubalis) milk: A three year study

Abstract: Buffalo milk represents an indispensable source of nourishment in many parts of the world and it is the second most consumed milk worldwide. Buffalo milk is actually used for the production of many dairy products such as pasteurized or concentrated milk, butter, yogurt, ice-cream, dehydrated milk products and cheeses. Due to its high nutritional value and the presence of natural bioactive substances, buffalo milk can also provide health benefits to consumers. In Italy, buffalo milk is used mainly for cheese ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 31 publications
8
36
3
4
Order By: Relevance
“…The results indicate that the Kızılırmak Delta is still being contaminated with some OCP and PCB compounds. The residual levels of PCBs predominated, followed by in-PCBs, DDTs, beta-HCH, gamma-HCH, alpha- Although buffalo milk is the second most consumed milk worldwide (Pasquini et al, 2018), there have been limited reports on PCBs (Cirillo et al, 2008;Esposito et al, 2010;Santelli et al, 2006) and OCPs (Abbassy, 2017;Aslam et al, 2013;Barman and Mishra, 2015;Bulut et al, 2011;John et al, 2001;Makadiya and Pandey, 2017;Sajid et al, 2016;Shaker and Elsharkawy, 2015). However, comparing the results was not feasible as the researchers did not state the OC levels in water buffalo milk on fat weight basis except a small number of studies (Abbassy, 2017;Aslam et al, 2013;Bulut et al, 2011;Cirillo et al, 2008;Esposito et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that the Kızılırmak Delta is still being contaminated with some OCP and PCB compounds. The residual levels of PCBs predominated, followed by in-PCBs, DDTs, beta-HCH, gamma-HCH, alpha- Although buffalo milk is the second most consumed milk worldwide (Pasquini et al, 2018), there have been limited reports on PCBs (Cirillo et al, 2008;Esposito et al, 2010;Santelli et al, 2006) and OCPs (Abbassy, 2017;Aslam et al, 2013;Barman and Mishra, 2015;Bulut et al, 2011;John et al, 2001;Makadiya and Pandey, 2017;Sajid et al, 2016;Shaker and Elsharkawy, 2015). However, comparing the results was not feasible as the researchers did not state the OC levels in water buffalo milk on fat weight basis except a small number of studies (Abbassy, 2017;Aslam et al, 2013;Bulut et al, 2011;Cirillo et al, 2008;Esposito et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Buffalo milk is a preferential food source in different parts of the world and the second most consumed milk in the worldwide and in Europe. Italy, Turkey, Bulgaria and Greece are the countries where the largest amounts of buffalo milk being produced (Pasquini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a comprehensive discussion on composition traits was difficult, due to the paucity of works in literature investigating the effect of month of calving on FC, PC, LC, and SCS. In fact, only the effect of the month of sampling has been widely investigated in buffaloes [31] with the greatest (8.54%) and the lowest FC (6.27%) estimated for milk sampled in January and June, respectively. Similarly, some studies reported greater FC in milk sampled in winter [32,33].…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Regarding fat and protein components, in fact, there is a general accordance on the presence of seasonality ( 34 38 ). For SNF, our study assessed seasonality not confirmed by other authors ( 33 , 34 ), even though both cited papers reported statistically significant increase of SNF component in early autumn.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, which encompassed three complete years, careful planning of data collection procedures led to a complete dataset of 110 measurements without any missing data. Seasonality presence, usually investigated through linear ANOVA models ( 33 ), was assessed in method B using Friedman's test on monthly averaged data, which, being non parametric, does not need normality assumption, a condition than can be unmet in practice, and which is usually addressed through logarithmic transformations ( 23 ). This study's choice, while being relatively irrelevant for the implementation of control chart techniques—which are considered to be robust to deviation from normality ( 16 )—may however represent in advantage in assessing the presence (or absence) of seasonality on collected milk parameters.…”
Section: Discussionmentioning
confidence: 99%